Isolation and Characterization of Collagen and Nanocollagen from Snakehead Fish (Channa Striata) Bone: formulation and evalution effervescent floating tablet - Dachi, Kanne; Reveny, Julia; Arianto, Anayanti (Asian Journal of Pharmaceutical Research and Development, 2020)
Objective: This study aims to find out the collagen compounds of the isolation result of the fish bones of the Snakehead have fulfilled the standard of fish collagen and can be formed into nanocollagen. Methods: All extraction processes are conducted at 4 0C. Snakehead's bones are soaked with a solution of NaOH 0.1 M with a ratio of 1:10 for 12 hours with occasional stirring, immersion is performed twice every 6 hours (pre-treatment process), then neutralized with bidistilled water up to pH 7. Extracted with a solution CH3COOH 0.5 M with a ratio of 1:10 for 3 days (check pH), added bidistilled water until pH 4.6. The filtrate is centrifuged at a speed of 4000 rpm for 15 minutes (the residue obtained is extracted back by the same treatment). Acquired Supernatan added 10% NaCl is allowed for 24 hours (collagen precipitate). The precipitate is dried in an oven with a temperature 40 0C for 24 hours, the sample is dry mashed, collagen powder obtained. Results: Moisture content and an ash content of the collagen's bone isolation is obtained at 0.50%. The protein content of the cored collagen is 85.20%. The existence of fat in the collagen of the Snakehead fishbone is an impurities element that needs to be eliminated through the pretreatment process optimization. Conclusions: Collagen compounds result from the isolation of the Snakehead fish bones meet the standard of fish collagen, including moisture content, ash content, protein levels, and fat levels and can be formed into nanocollagen.